Amyloid-peptide β 42 Enhances the Oligomerization and Neurotoxicity of apoE4: The C-terminal Residues Leu279, Lys282 and Gln284 Modulate the Structural and Functional Properties of apoE4. (1st December 2018) - Dafnis, Ioannis; Argyri, Letta; Chroni, Angeliki
Highlights: ApoE4 forms SDS-stable oligomers, which are increased following the incubation of apoE4 with Aβ42. Aβ42 enhances apoE4's cytotoxicity. C-terminal conserved residues L279, K282 and Q284 of apoE4 affect protein's structural and conformational properties. C-terminal residues L279, K282 and Q284 of apoE4 are involved in oligomerization and cytotoxicity of apoE4. The conformation and oligomerization of apoE4 may underlie the protein's functional properties related to neurotoxicity. Abstract: Apolipoprotein E4 (apoE4), one of the three apoE isoforms, is the strongest factor for raising the risk for late-onset Alzheimer's disease (AD) and has been proposed to play a major role in AD pathogenesis. Amyloid-peptide β 42 (Aβ42) has also been proposed to affect neuronal degeneration and AD pathogenesis, possibly by interacting with apoE. Previous studies have shown that the functions of apoE forms can be dictated by their structural and biophysical properties. Here we show that apoE4 can form SDS-stable oligomers, possibly reflecting aggregated forms, which increase following incubation of apoE4 with Aβ42. In addition, extracellular apoE4 is cytotoxic for human neuroblastoma SK-N-SH cells, while Aβ42 enhances the cytotoxicity of apoE4. Carboxyl-terminal point mutations L279Q, K282A or Q284A reduced the capacity of apoE4 to form SDS-stable oligomers, as well as its cytotoxicity, both in the absence and presence of Aβ42. Structural and thermodynamic analyses showed that all three apoE4 mutants have significantly increased α-helical and decreased β-sheet content, have reduced portion of hydrophobic surfaces exposed to the solvent and have a reduced conformational stability during chemical denaturation. Overall, our data highlight a pathogenic role of apoE4 that could be linked to the capacity of the protein to form oligomeric species especially in the presence of Aβ42 and to induce cytotoxicity. Carboxyl-terminal residues L279, K282 or Q284 appear to be involved in the conformation of apoE4 that may underlie the protein's functional properties related to neurotoxicity.